Some new forms of functional social control in the Netherlands and their effects - Toornvliet, Leo; Zandbergen, Anke; Hofstra, Bart (The British journal of criminology, 1996)
Recent government policy in the Netherlands has supported the introduction of a number of new types of agents of social control. This article, based on the results of two recent research projects (Hauber et al. 1993a, b), focuses on three questions central to the effectiveness and acceptability of three kinds of agents: city wardens, police patrollers, and public transport inspectors. First, objective security: what effects did supervision by different types of agents have on those forms of crime with which the agents were confronted, as observed by the researchers? Secondly, the performance of the agents and the reactions of the members of the public with whom they were in contact will be discussed. Finally, subjective security will be discussed: did the agents have a positive influence on the public's perception of their safety?